Differences of body dimensions in female volleyball players (cadets) in relation to volleyball playing position - Vujmilovic, A.; Karalic, T. (The Sport Journal, 2014)
This research presents a test of the hypothesis that there are differences in morphological characteristics, which affect effective realization of the elements of the game, which are influenced by many factors from the area of anthropological status of the volleyball players. The study examines the relations of body-dimensions of cadet female volleyball players and provides the answers to a question of how different are they in that segment, depending on which position in the team they play. The research was conducted on a sample of 55 female volleyball players. The sample was grouped as follows: opposites, middle blockers, outside hitters, setters and liberos. To determine the physical size differences between groups, the authors used the univariate analysis of variance (ANOVA), while for the precise determination of the sources of variability between groups the authors used a Post Hoc analysis, Tukey HSD test as a method of multiple comparisons. A model of physical dimensions was used, that contains the five (5) variables: body height (ATV), range of hands (RAR), body weight (ATT), maximum reach with one hand from a place (MDOH1RM) and maximum reach with two hands from a place (MDOH2RM). With this model the differences have been found in body height (ATV) p=0.001, range of hands (RAR) p=0.003, maximum reach with one hand from a place (MDOH1RM) p=0.000, and maximum reach with two hands from a place (MDOH2RM) p=0.000. Based on the results of a post hoc analysis, statistically significant differences have appeared between the group Liberos and other groups of specialists. In scientific research practice there is a lack of research of this kind. In this sense, this research is conceived as a small contribution to the advancement of the profession especially in the domain of training technologies and optimal functioning of female volleyball players in training process, and manner of its planning and programming.